posted by .

how do you solve this?

x+4/x^2-x-6 + 3x-2/x^2+3x+2

  • algebra -

    We have 2 fractions here. The first thing you want to do is equal the entire expression to 0 (in order to solve for x).

    So we get that:

    ((x+4)/(x^2-x-6))+ ((3x-2)/(x^2+3x+2))=0

    Now, we can transfer one of the fractions to the other side of the equation. We get that:

    ((x+4)/(x^2-x-6)) = ((2-3x)/(x^2+3x+2))

    Now, if we mulitply each of the denominators of the fractions with the numerators at the other side of the equation, we get that:

    (x+4)*(x^2+3x+2) = (2-3x)*(x^2-x-6)
    When we use the distributive rule, we find that:

    => x^3+7x²+14x+8=-3x^3+5x²+16x-12

    Now, if we transfer one side to the other, we get that:

    if we divide both sides by 2, we get that:


    Now, I don't know if you're familiar with factoring a polynomial, but that is in fact the best way to go. I won't go into depth into this subject, but when you factor this polynomial, you get the equation:


    When we calculate the discriminant for the second factor in the equation, we find that it equals -31, so its negative. This means that the second factor (2x²-3x+5) has no further solutions. So, the only time this equation becomes zero is when x=-2 (because the first factor of the equation (x+2) becomes zero when x=-2).

    So -2 is a solution for this equation. Our work doesn't stop here. Since we had some polynomials in denominators in thr original equation, we have to check that the denominators don't become zero for x=-2. Otherwise, -2 isn't a solution for the equation. When we fill in -2 in both denominators, we notice they both become zero. So, since -2 isn't a solution for the equation after all, we find that the equation has no solutions.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Algebra

    FIND THE GCF OF THE PRODUCT (3B+6)(2B-10) SOLVE... X^2=-6X x(x+6)= 0 x = -6 or 0 it would = 0 help me solve this problem.. solve for W: 2L+2W=38 please and thank you!
  2. Intermediate Algebra

    Combine like terms: -3x^2+2x-4x^2-9+6x-2x^2+8 Solve for x: 8x-11= -11x+18 Solve for x: -2(x-5)+7=z-8-5x Solve for x: (x-2)/5 - 3/2= (x+1)/10 Translate to an algebra statement; do not solve: Seven times the difference of six and a twice …
  3. Algebra 2

    Solve each system 3x+2y= -2 9x- y= -6 I know how to solve for x but i get really lost trying to figure out how to solve for the second variable
  4. algebra

    Solve the indicated variable: 1. Volume of a cone: solve for h: V=¨ir^2h/3 2. Temperature formula: solve for C: F=9/5C+32 pleaseeeee help me solve these! plzzz! i have nooo idea how to do these. THANKS! =)))
  5. algebra

    solve for the indicated variable: a. temperature formula solve for F: K=5/9(F-32)+273 b. annual interest rate solve for R: A=P+Prt
  6. Algebra

    Hi, how would I solve these 2 equations using algebra?
  7. Math

    We have an important chemsitry test due and I want to make sure that I do not mess up on my algebra. I am dealing with the integrated rate law, but my question is purely algebraically in nature. I hope, somebody can help me. 1) ln(A) …
  8. algebra

    im trying to solve a literal equation, then solve the specific question first part is stumping me, im to solve for X ax=bx-c this is what I got ax-bx=c, but don't know how to get x by itself
  9. Algebra

    Solve for x: h=(k/4)(x-3L) Solve for B: v-6Bxk=7B Solve for S: z+(1/7)sk=(1/6)yk^2 Solve for x: 3F=10hx+10hv+10xv
  10. Algebra 2

    How do I solve these inequalities: e^3x>e^x-1 -6log (subscript of 4) x > -24 & how do I solve these: 8^x+1=3 e^x+2=50 8logx=16 I really don't understand how to solve these so can someone please explain them to me?

More Similar Questions